Purification and characterization of polyclonal anti-hepatitis B core antigen immunoglobulin G from rabbit serum - Sayed Hitam, Sharifah Mariam (2016)
Antibodies are biologically active proteins produced by plasma cells in response to the presence of foreign substances. Antibodies such as immunoglobulin G (IgG) have been used extensively for diagnostic and therapeutic purposes. Polyclonal antibodies against hepatitis B core antigen raised in rabbits that react to diseases can be used as medication for human subjects. Protein A affinity chromatography, has been a standard method used to purify antibodies for the past few decades due to its high affinity to antibodies efficient product capture. However, this approach has a number of disadvantages, especially in large scale applications due to its low ligand stability and high production cost. Thus, a simple and economical method for antibody purification via precipitation and adsorption chromatography in combination with hydrophobic and ion exchange approaches, was investigated as an alternative to overcome this problem.The development of simple and short execution time as well as low cost techniques for antibody separation and purification by ammonium sulfate precipitation was examined in the current study. Salting out with different percentages of ammonium sulfate was introduced as an early step in this study to separate IgG from other serum impurities. Serum albumin is the main challenge in this purification process, as it is a major contaminant in the serum. From the precipitation study in a single purification system, 40% of ammonium sulfate saturation gave the best result in terms of the concentration of IgG recovered (7.8 mg/mL) and albumin removal (27.9 mg/mL). From the observations, concentrations of saturated ammonium sulfate (SAS) greater than 40% caused the precipitation of serum albumin together with the IgG, hence reducing its purity. At this ideal condition, the yield, purity and purification factor were 99%, 94% and 7.8, respectively. Besides, due to the incorporation of salt in this method, the final product showed high value of conductivity, which was 16 ± 1 mS/cm. Moreover, its high ionic strength could affect the productivity of the purified antibody as it would shield the active sites of the protein. Thus, SepFastTM MM AH-1 which has a combination of anionic and hydrophobic groups was introduced to be incorporated with the salt precipitation method. The integrated system approach showed a promising result as it successfully reduced the ionic strength by up to 75%. Due to this, the need of desalting the final product was abolished. At the final polishing process, the yield and purity of the polyclonal IgG also showed a good improvement as it increased to 97% and 98%, relatively. In comparison to salt precipitation, the IgG recovered by the coupling method with mixed mode column was significantly more productive as it produced mostly monomeric immunoglobulin. Besides, a monomodal regularisation histogram revealed the particle size distribution of the polyclonal IgG recovered from rabbit serum as being about 10.3 nm in diameter, which is equivalent to the reported size of IgG. The efficiency of the single-step purification approach based on prepacked SepFastTM Supor DEAE column for the purification of the anti-HBcAg IgG from rabbit serum was also evaluated in this study. Furthermore, the optimal pH, which was determined as pH 8.0, offered the highest recovery of IgG of about 20% from the total proteins. This single step of purification showed excellent recovery with yield and purity at about 94% and 83%, which corresponded to 7.4 purification factor. The aggregation study by dynamic light scattering (DLS) revealed that the molecular size of the anti-HBcAg IgG from rabbit serum was around 10 nm, which is equivalent to the native IgG. In conclusion, this study shows that SepFastTM MM AH-1 column has a great potential to be used in the polishing step as it is able to reduce the ionic strength of the sample solution and to separate the monomers from its aggregates. Besides, SepFastTM Supor DEAE column chromatography shows potential application at industry scale to purify IgG with only a single step of application.